2001
DOI: 10.1161/hh1201.092042
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus Enhances Vascular Matrix Metalloproteinase Activity

Abstract: Abstract-Diabetes mellitus (DM) is a primary risk factor for cardiovascular disease. Although recent studies have demonstrated an important role for extracellular matrix metalloproteinases (MMPs) in atherosclerosis, little is known about the effects of hyperglycemia on MMP regulation in vascular cells. Gelatin zymography and Western blot analysis revealed that the activity and expression of 92-kDa (MMP-9) gelatinase, but not of 72 kDa (MMP-2) gelatinase, were significantly increased in vascular tissue and plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
290
5
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 439 publications
(320 citation statements)
references
References 53 publications
(37 reference statements)
19
290
5
6
Order By: Relevance
“…However, short-term hyperglycaemia (24-h) was not able to induce the same alteration [50]. In this study, we studied the effect of high plasma glucose concentrations on myocardial perfusion in Type I diabetic patients.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, short-term hyperglycaemia (24-h) was not able to induce the same alteration [50]. In this study, we studied the effect of high plasma glucose concentrations on myocardial perfusion in Type I diabetic patients.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, it has been found that during chronic hyperglycaemia, endothelial cells' metalloproteinases are activated, indicating a mechanism by which poor glycaemic control could increase the risk for atherosclerotic complications [50]. However, short-term hyperglycaemia (24-h) was not able to induce the same alteration [50].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress, triggered partially by reactive oxygen species (ROS) causes endothelial cell dysfunction, cellular injury, and tissue damage, which can contribute to the pathology of atherosclerosis (Kuzkaya et al 2003) and other vascular diseases Landmesser et al 2001;Uemura et al 2001;Cooke 2004). O 2 .-and other ROS may have a key role in the early development of atherosclerosis, even prior to lesion development as increases in ROS are associated with many disease risk factors (Kuzkaya et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 20%-40% of patients with type 1 diabetes and 10%-20% of those with type 2 diabetes develop nephropathy (Deckert et al, 1981). Hyperglycaemia can cause diabetic complications, several biochemical markers can indicate pathogenesis, including advanced glycation end-products (AGEs) (Masutani et al, 1999;Nakajou et al, 2005), reactive oxygen species (ROS) (Uemura et al, 2001), mitogen-activated protein kinase (MAPK) , protein kinase C (PKC) (Craven et al, 1990), transforming growth factor-β (TGF-β) (Bottinger and Bitzer, 2002), poly (ADP-ribose) polymerase (PARP) (Minchenko et al, 2003), platelet-derived growth factor (PDGF) (Tsiani et al, 2002) and endothelin (Ding et al, 2003).…”
Section: Introductionmentioning
confidence: 99%